Phonology in the Twentieth Century Second edition, revised and expanded (Volume 5) - Anderson, Stephen R. (Language Science Press, 2021)
The original (1985) edition of this work attempted to cover the main lines of development of phonological theory from the end of the 19th century through the early 1980s. Much work of importance, both theoretical and historiographic, has appeared in subsequent years, and the present edition tries to bring the story up to the end of the 20th century, as the title promised. This has involved an overall editing of the text, in the process correcting some errors of fact and interpretation, as well as the addition of new material and many new references.